S87 Greater exercise tolerance in COPD during acute intermittent compared to endurance shuttle walking protocols: a proof-of-concept study. (11th November 2022) - Alexiou, C; Chambers, F; Megaritis, D; Wakenshaw, L; Echevarria, C; Vogiatzis, I
Abstract : Introduction: Ground-based walking is a simple training modality which would suit pulmonary rehabilitation (PR) settings with limited access to specialist equipment. Patients with advanced COPD are, however, unable to walk uninterruptedly at a relatively fast walking pace to optimise training benefits. Objective: To compare walking distance and circulatory responses between an intermittent (IntSWT) and an endurance shuttle walking (ESWT) protocol. Methods: In this cross-sectional study we measured in 14 COPD patients (mean±SD FEV1 : 45±21% predicted), walking distance, cardiac output (CO), heart rate (HR), arterial oxygen saturation (SpO2 ), and symptoms during (a) IntSWT, consisting of 1-min walking alternating with 1-min rest, and (b) ESWT, both sustained at 85% of peak VO2 predicted to the limit of tolerance (Tlim). Results: Median (IQR) distance and endurance time were greater (p=0.001) during IntSWT [735 (375–1107) m and 19.61 (19.0–28.8) min, respectively] compared to ESWT [190 (117–360) m and 3.23 (2.32–5.75) min, respectively]. At iso-distance (distance at Tlim during ESWT) IntSWT compared to ESWT was associated with lower CO (8.6±2.6 versus 10.3±3.7 L/min; p=0.013), HR (96±14 versus 103±13 beats/min; p=0.001), greater SpO2 (92±6 versus 90±7 %; p=0.002), and lower symptoms of dyspnoea (2.8±1.3 versus 4.9±1.4; p=0.001) and leg discomfort (2.3±1.7 versus 4.2±2.2; p=0.001). Furthermore, throughout the walking tests, IntSWT compared to ESWT was associated with lower symptoms of dyspnoea (p=0.001), and leg discomfort (p=0.03) ( figure 1 ). However, at Tlim symptoms of dyspnoea and leg discomfort were not different between IntSWT and ESWT, suggesting that the major reasons for limiting walking endurance in both modalities were having reached comparable intensity of symptoms, which took longer during IntSWT compared to ESWT. Conclusion: IntSWT may provide important clinical benefits in the PR settings because it is sustained with lower symptoms, thereby allowing greater work outputs compared to ESWT.